Designing & simulation of a lightweight hip implant stem: an FEM based approach. (31st October 2022) - Sahai, Nitin; Saxena, Kuldeep K.; Gupta, Nakul; Garg, Sahil; Bora, Uddipta; Baishya, Utpal Jyoti; Borah, Volga
ABSTRACT: Total hip arthroplasty is a widely used surgical intervention widely used in entire world. Objective of this paper is to develop a hollow lightweight costeffective model of hip implant stem using CAD and optimise it for better results than the already existing designs. The study therefore focuses on designing and simulation of a lightweight, cost-effective and durable model of prosthetic hip implant. The developed design is optimised in such a way that revascularisation in bone tissue reduces the weight of the implant stem. This is done by punching holes in the distal end of the design module. Standard boundary conditions are applied using ASTM F2996-13 with tetrahedral mesh elements for static structural analysis. From comparative study between three Ti6Al4V models (viz. solid model, model with 3 mm holes and model with 4.5 mm holes), it can be stated that the model with 3 mm holes was superior. This model showcases lower weight as well as lower values of all the static structural analysis performed. Model with 3 mm holes was approximately 15% lighter than solid reference model and experiences around 100 MPa lesser Von Mises stress than that experienced by model with hole sizes of 4.5 mm.